Enhancing the Antioxidant, Anti-tyrosinase and Anti-elastase Activity of Pigmented Rice Extracts by Sonication, Heating, Enzyme Digestion and Fermentation - Nathkhaanthaphot, Nathnaphads; Pongdontri, Paweena; Riddech, Nuntavun; Theerakulpisut, Piyada (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
In the modern cosmetics industry, there exists a major trend for replacement of synthetic chemicals with plant-based ingredients in skincare formulation. This research aimed to assess the efficiency of different methods to extract bioactive compounds (as measured by total phenolic content; TPC and total flavonoid content; TFC) responsible for three important cosmeceutical properties (antioxidation, anti-tyrosinase, and anti-elastase) from selected rice grains. The grains of two varieties of purplish-black rice (Neaw Leum Pua; NLP) and black rice (Hom Nil; HN) were extracted with phosphate buffered saline (PBS) and then supplementary treated with sonication, heating, and proteolytic enzyme digestion or fermented with Aspergillus niger. The results showed that sonication slightly enhanced TPC and TFC, but significantly increased antioxidant capacity and anti-tyrosinase activity. The high temperature of 60℃ and 100℃ significantly increased antioxidant capacity based on FRAP assay but reduced that based on DPPH radical scavenging assay. Anti-tyrosinase activity was enhanced by high temperature but that of anti-elastase was inhibited. The addition of papain to the seed extracts slightly enhanced anti-elastase and anti-tyrosinase activity. Notably, fermented rice grains exhibited much greater yields of TPC and TFC, and higher biochemical activities than other methods. The fermented rice exhibited the highest TFC after 3 days; the highest TPC, antioxidant capacity, and tyrosinase inhibition after 6 days; and the highest elastase inhibition activity after 9 days. Therefore, fermentation was the most promising technique to enhance all three desirable properties for cosmetic ingredients when pigmented rice was used as the raw material.